Thermal Instability in a Model Chain Branching - Chain Breaking Kinetics - Ajadi, S. O. (2014)
Thermal instabilities such as thermal explosion and thermal ignition are examined in a two-step reactions mechanism, comprising of a chain-branching and a chain-breaking step. The aim of this study is to examine the influence of the chain-breaking step on these instabilities and then compare our findings with the existing results for the one step model, which is mainly a branching step. The resulting mathematical equations were subjected to a variational method executed on the Mathematics package for the analysis of thermal explosion, while the thermal ignition is amenable to simple integration. These results show that the chain branching step leads to a complete departure from existing results for the one step model. It is established that the Frank-Kamenetskii parameter and the ignition time are monotonically decreasing functions of the heat parameters.